Antibiotic resistance in severe odontogenic infections of the South Australian population: a 9‐year retrospective audit. (10th May 2018) - Liau, I; Han, J; Bayetto, K; May, B; Goss, A; Sambrook, P; Cheng, A
Abstract: Background: The aims of this study were to evaluate the microbiological trends in severe odontogenic infections requiring hospital admission in the South Australian Oral and Maxillofacial Surgery Unit. Rates of antibiotic resistance to empirical antibiotic regimens were determined to quantify the clinical implications of antibiotic‐resistant odontogenic infections. Methods: A retrospective case audit was performed on all odontogenic infections admitted to the Royal Adelaide Hospital over a 9‐year period. Data was collected regarding demographics, microbiological culture and sensitivity results, and clinical outcome variables. Results: Of a total of 672 patients, microbiology data was available for 447 cases. Penicillin‐resistant organisms were identified in 10.8% of patients, who required a significantly longer length of hospital admission (mean, 9.93 days) and higher rates of non‐response to initial surgical therapy (40%). Conclusions: There were moderate rates of antibiotic‐resistant odontogenic infections within the South Australian population. Patients within this subgroup demonstrate markedly poorer clinical outcomes. Effective treatment of odontogenic infections involves early operative intervention, with adjunctive use of appropriate antibiotic therapy that involves close monitoring of response to removal of the cause and use of first‐line antibiotic agents. Cases that fail to respond require urgent specialist review in order to reduce morbidity and mortality outcomes.